The tip of the iceberg: ROP2 directly interacts with SYP121 to regulate root-hair polarization, elongation, and exocytosis - Ricardi, Martiniano María (2022)
Root hairs (RHs) grow in a polar manner as cylindrical protrusions from the root epidermis. They significantly expand the root volume in the rhizosphere to search for water and nutrients, anchor the plant, and promote interactions with several kinds of microorganisms in the soil. Trichoblasts, the epidermis cell type responsible for RH development, switch from anisotropic cell elongation to tip growth through polarization of the growth machinery to a predefined RH initiation domain (RHID) at the plasma membrane.